The effect of age and amount of prohibited breastfeeding A comparative jurisprudence study (Journal of the College of Basic Education, 2022)
- The research showed that breastfeeding is composed of three main elements; Breastfeeding, milk, and a breastfeeding woman, and each of them has its own conditions according to the jurists, some of which are agreed upon, while others are different.- The age of the infant, if it is less than three years, and the breastfeeding process took place under its other conditions, has an effect on the fulfillment of sanctity, but what is more than that has no effect on the public, and the phenomenon considers that the entire age is influential.- The amount of milk that the infant takes, in order for it to have an effect on the prohibition, some of its signs must appear, such as satisfying his hunger, growing flesh, or breaking bones, and the growth of a body, in a difference of opinion among the jurists.There are seven taboos for breastfeeding, just as there are seven taboos for lineage.